Thin film growth of the Weyl semimetal NbAs - Yánez Parreño, Wilson (2024)
We report the synthesis and characterization of thin films of the Weyl semimetal NbAs grown on GaAs (100) and As-terminated GaAs (111)B substrates. By choosing the appropriate substrate, we can stabilize the growth of NbAs in the [001] and [100] directions. We combine x-ray characterization with high-angle annular dark field scanning transmission electron microscopy to understand both the macroscopic and microscopic structure of the NbAs thin films. We show that these films are textured with domains that are tens of nanometers in size and that, on a macroscopic scale, are mostly aligned to a single crystalline direction. We describe electrical transport measurements that reveal similar behavior in films grown in both crystalline orientations, namely resistivity in the range 420-450 µΩ.cm and carrier densities in the range ∼10^21–10^22 cm^(-3) at 2 K. Finally we measure spin to charge conversion in NbAs and show that it qualitatively agrees with first principles calculations.